Analysis on logic in Mi‛yār al-‛Ilm fī Fann al-Mantiq - Yaman Towpek,; Kamaruddin Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Mi‛yār al-‛Ilm fī Fann al-ManÏiq of al-Ghazālī is the first book on Islamic logic. But a specific, comprehensive and exclusive study on its essence of the scientific contents and its importance in developing scientific thinking has never been done yet. Therefore, this study investigated qualitatively the background of Mi‛yār and its contents using content analysis. In this study, the data which were collected using documentation method has been analyzed using the inductive, deductive and comparative methods. The process of analysis on logic in Mi‛yār also been done using textual analysis method or textual content analysis method. This is because it is textual study. This study found that the theories, methods and thoughts on logic in Mi‛yār have several similarities and differences with the logic of Aristotle. This study also found that many reforms, improvements, purifications and reconciliations have been made in Mi‛yār which uplifted the theories on logic in Mi‛yār as the theories of Islamic logic. In addition, this study found that the examples of logic application in Mi‛yār are highly relevant to the life of a Muslim. Mi‛yār should be a basic source of learning on logic and thinking methods of Muslims either in secondary schools or universities. Hence the constant and deep study on the content of Mi‛yār is very significant and has high impact. But the dissemination of the output of this study is the next action that should be realized.